Nanoparticle Counting for PTI: The Dirty Tail Paradigm — A Pragmatic Proposal to Strongly Reduce Urban PN Pollution from Combustion Engine Fleets - A. Mayer; J. Czerwinski; Th. Lutz; F. Legerer; M. Wyser; P. Comte; L. Larsen; L. Rubino; K. Vasilatou; D. Engelmann; M. Knoll; H. Burtscher (Emission Control Science and Technology, 2025)

P24-01 Impact of perinatal and subchronic dietary glyphosate exposure on gut microbiota and liver metabolism in mice - C.M.P. Martin; L. Smith; L. Evariste; F. Lasserre; A. Polizzi; V. Alquier-Bacquie; C. Dauriat; B. Engelmann; U. Rolle-Kampczyk; M. Von Bergen; B. Lamas; E. Houdeau; et al. (Toxicology Letters, 2024)

A parsimonious approach to predict regions affected by sewer-borne contaminants in urban aquifers - Karen L. Rojas-Gómez; Martin Binder; Marc Walther; Christian Engelmann (Environmental Monitoring and Assessment, 2023)
Leaky urban drainage networks (UDNs) exfiltrating wastewater can contaminate aquifers. Detailed knowledge on spatiotemporal distributions of water-dissolved, sewer-borne contaminants in groundwater is essential to protect urban aquifers and to optimize monitoring systems. We evaluated the effect of UDN layouts on the spreading of sewer-borne contaminants in groundwater using a parsimonious approach. Due to the UDN’s long-term leakage behavior and the existence of non-degradable sewer-borne contaminants (equivalent to a conservative and constant contaminant source), we employed a concept of horizontal line sources to mimic the UDN layout. This does not require the consideration of bio-degradation processes or temporal delay and effectively bypasses the vadose zone, thus reducing computational requirements associated with a full simulation of leakages. We used a set of synthetic leakage scenarios which were generated using fractals and are based on a real-world UDN layout. We investigated the effects of typical leakage rates, varying groundwater flow directions, and UDN’s layouts on the shape of the contaminant plume, disregarding the resulted concentration. Leakage rates showed minimal effects on the total covered plume area, whereas 89% of the variance of the plume’s geometry is explained by both the UDN’s layout (e.g., length and level of complexity) and groundwater flow direction. We demonstrated the potential of applying this approach to identify possible locations of groundwater observation wells using a real UDN layout. This straightforward and parsimonious method can serve as an initial step to strategically identify optimal monitoring systems locations within urban aquifers, and to improve sewer asset management at city scale.

The role of phase transition by inception and surface reactions for the synthesis of silicon nanoparticles in a hot-wall reactor – Simulation and experiment - P. Wollny; L. Engelmann; M. Loewenich; I. Rahinov; H. Wiggers; C. Schulz; A. Kempf; I. Wlokas (Chemical Engineering Journal, 2023)

The role of phase transition by nucleation, condensation, and evaporation for the synthesis of silicon nanoparticles in a microwave plasma reactor — Simulation and experiment - P. Wollny; J. Menser; L. Engelmann; J. Sellmann; C. Schulz; H. Wiggers; A. Kempf; I. Wlokas (Chemical Engineering Journal, 2023)

A mosaic of induced and non‐induced branches promotes variation in leaf traits, predation and insect herbivore assemblages in canopy trees - Martin Volf; Tereza Volfová; Carlo L. Seifert; Antonia Ludwig; Rolf A. Engelmann; Leonardo Ré Jorge; Ronny Richter; Andreas Schedl; Alexander Weinhold; Christian Wirth; Nicole M. van Dam (Ecology Letters, 2022)
Forest canopies are complex and highly diverse environments. Their diversity is affected by pronounced gradients in abiotic and biotic conditions, including variation in leaf chemistry. We hypothesised that branch‐localised defence induction and vertical stratification in mature oaks constitute sources of chemical variation that extend across trophic levels. To test this, we combined manipulation of plant defences, predation monitoring, food‐choice trials with herbivores and sampling of herbivore assemblages. Both induction and vertical stratification affected branch chemistry, but the effect of induction was stronger. Induction increased predation in the canopy and reduced herbivory in bioassays. The effects of increased predation affected herbivore assemblages by decreasing their abundance, and indirectly, their richness. In turn, we show that there are multiple factors contributing to variation across canopies. Branch‐localised induction, variation between tree individuals and predation may be the ones with particularly strong effects on diverse assemblages of insects in temperate forests.

Pro- and anti-inflammatory macrophages express a sub-type specific purinergic receptor profile - J. Merz; A. Nettesheim; S. von Garlen; P. Albrecht; B. S. Saller; J. Engelmann; L. Hertle; I. Schäfer; D. Dimanski; S. König; L. Karnbrock; K. Bulatova; et al. (Purinergic Signalling, 2021)
Extracellular nucleotides act as danger signals that orchestrate inflammation by purinergic receptor activation. The expression pattern of different purinergic receptors may correlate with a pro- or anti-inflammatory phenotype. Macrophages function as pro-inflammatory M1 macrophages (M1) or anti-inflammatory M2 macrophages (M2). The present study found that murine bone marrow-derived macrophages express a unique purinergic receptor profile during in vitro polarization. As assessed by real-time polymerase chain reaction (PCR), Gαs-coupled P1 receptors A2A and A2B are upregulated in M1 and M2 compared to M0, but A2A 15 times higher in M1. The ionotropic P2 receptor P2X 5 is selectively upregulated in M1- and M2-polarized macrophages. P2X 7 is temporarily expressed in M1 macrophages. Metabotropic P2Y receptors showed a distinct expression profile in M1 and M2-polarized macrophages: Gαq coupled P2Y 1 and P2Y 6 are exclusively upregulated in M2, whereas Gαi P2Y 13 and P2Y 14 are overexpressed in M1. This consequently leads to functional differences between M1 and M2 in response to adenosine di-phosphate stimulation (ADP): In contrast to M1, M2 showed increased cytoplasmatic calcium after ADP stimulation. In the present study we show that bone marrow-derived macrophages express a unique repertoire of purinergic receptors. We show for the first time that the repertoire of purinergic receptors is highly flexible and quickly adapts upon pro- and anti-inflammatory macrophage differentiation with functional consequences to nucleotide stimulation.

A simple protocol for cryopreservation of zygotic embryos of ten accessions of coconut (Cocos nucifera L.) - O. N’Nan; M. Borges; J.-L. Konan Konan; V. Hocher; J.-L. Verdeil; J. Tregear; A. S. P. N’guetta; F. Engelmann; B. Malaurie (In Vitro Cellular & Developmental Biology - Plant, 2012)

Earthworm leukocyte populations specifically harbor lysosomal enzymes that may respond to bacterial challenge - P. Engelmann; L. Molnr; L. Plinks; E. L. Cooper; P. Nmeth (Cell and Tissue Research, 2004)